Control of Enzyme Reactivity in Response to Osmotic Pressure Modulation Mimicking Dynamic Assembly of Intracellular Organelles - Schvartzman, Clémence (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.